FLEKSIBILITAS REKONFIGURASI ATURAN KETENAGAKERJAAN SEBAGAI MODE HIBERNASI USAHA PT CAHAYA BUKIT PERUNGGU (CBP) - Siti Aesah (Universitas Dharmawangsa, 2026)
The COVID-19 pandemic forced manufacturing firms to redesign labour rules and operational practices in order to maintain business continuity under severe demand and supply uncertainty. This study aims to formulate a flexible reconfiguration strategy for labour arrangements in factory operations and to test the business hibernation mode at PT CBP, a manufacturing firm producing lamp housings. The study used a quantitative approach with exploratory factor analysis. Data were collected through questionnaires distributed to 29 respondents consisting of internal employees and external stakeholders. Thirteen indicators were analysed using principal component analysis with varimax rotation in SPSS. The Kaiser-Meyer-Olkin value was 0.821 and Bartlett's test was significant at 0.000, indicating that the data were suitable for factor analysis. The results formed three components with a cumulative variance of 67.419%. The components represent digital-adaptive capability, business-continuity marketing capability, and operational efficiency with market protection. These findings indicate that business hibernation can be implemented through proportional working hours, proportional wages based on effective work, and flexible labour allocation according to order volume.